2015
DOI: 10.1186/s12877-015-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Stroke with atrial fibrillation or atrial flutter: a descriptive population-based study from the Brest stroke registry

Abstract: BackgroundIn the 1990s, epidemiological studies estimated the prevalence of stroke caused by atrial fibrillation (AF) at about 15 %. Given the aging population, there is a rise in the number of AF patients. AF prevention guidelines based on clinical practice and the literature have been published and updated since 2001. Implementation seems to have an impact on the prescription of vitamin K antagonist (VKA). During the last 20 years, few population-based studies have focused on the prevalence of atrial arrhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
2
6
1
Order By: Relevance
“…IS hospitalizations increased by 32% from 2000 to 2014, whereas AF-IS episodes more than doubled. Indeed, AF prevalence was 22.6%, which is within the range of 15% to 38% as previously described [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and increased along time ($0.9% per year), almost reaching 30% (i.e., 29.3% in 2014). An increasing prevalence of AF in patients with IS had already been described, but not to this extent-the results of both Jespersen et al [7] and Rosengren et al [41] showed an increase of approximately 0.4% per year.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…IS hospitalizations increased by 32% from 2000 to 2014, whereas AF-IS episodes more than doubled. Indeed, AF prevalence was 22.6%, which is within the range of 15% to 38% as previously described [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and increased along time ($0.9% per year), almost reaching 30% (i.e., 29.3% in 2014). An increasing prevalence of AF in patients with IS had already been described, but not to this extent-the results of both Jespersen et al [7] and Rosengren et al [41] showed an increase of approximately 0.4% per year.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, studies by Svennberg et al [65] and Lowres et al [67] describe examples from public health policies with good incremental cost-utility ratios between €3142 and €6267. As far as the second problem is concerned, achieving appropriate implementation of stroke prophylaxis guidelines in the real world has proved to be a true challenge, because many factors may play a role, including physicians' previous outcomes and difficulties with international normalized ratio targets, as compiled by Jannou et al [11], although the current availability of the direct oral anticoagulants is overcoming some of these concerns and inducing a higher preventive treatment implementation of AF-related stroke. Thus, the missed opportunities for stroke prevention in AF, highlighted by Gladstone et al [50] long ago, persist in our everyday practice, and our failure to implement quality improvement interventions over this time should persuade us once more to optimize stroke prevention and thus reduce their number and associated costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from recent population-based studies and registries also demonstrated that at least 25-30 % of all patients with an ischaemic stroke and >80 % of those with cardioembolic ischaemic stroke also had AF, suggesting a strong association between these two entities. 3,[33][34][35][36][37][38][39][40] Another important finding in this context was that stroke was the first manifestation of previously unknown AF in >25 % of AF-related strokes. 3,[33][34][35]41 This association was even higher if prolonged noninvasive or invasive monitoring was performed following a stroke.…”
mentioning
confidence: 95%
“…Although the risk of stroke associated with AFL is not higher than that associated with AF, studies have shown that high rates of conversion from AFL to AF and the risk of developing stroke itself are not negligible. 9,10,28 According to the logistic regression analysis, risk factors for ACU were being a woman, aspirin utilization, and limited anticoagulant options. Conversely, OAC therapy was better in patients with previous stroke experience, concurrent valvular heart disease, or CHF.…”
Section: Discussionmentioning
confidence: 99%